(3GdQSGdI GdMGJejI ef MceI CQSWGWGdjS hTYQ CHj GdWjH GdeJfHis - (3eMeO Hf GdMSf Hf GdeXaQ GdMGJej GdHZOGOj , CHh Ydj,J (B388 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfeG GMJcef Edjg fahS Ghdi GdfXQ hGfaGOJ dg HUGjQ Cgd GdacQ s
(3BNQgG (B:s
(3BNQ CaQGW GdeJhai Cbd ehGQO GdehJ JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B82s
(3eUOQ GbJfGA GdCUd (B:s
(3GeHQhRjGfG (B(10) s
Keywords: (3GdadSaI hGdefWbs